8 Comparison of the accuracy of flash versus prospectively acquired ct coronary angiography. (15th May 2019) - Liang, Kate; Dayer, Mark; Gosling, Oliver E
Abstract : Introduction: Computed Tomography Coronary Angiography (CTCA) is an accurate and established diagnostic tool. The development of ECG triggered spiral acquisition (FLASH) has allowed reduction in radiation dose whilst still providing diagnostic information. We aimed to compare the accuracy of FLASH and prospective CTCA acquisitions within our CT service. Method: Retrospective analysis of demographic and outcome data was performed for 2857 scans over a 69 month period (Feb 2013–Nov 2018). Results of CTCA and Invasive Coronary Angiography (ICA) were compared for patients having had FLASH or prospective scan protocols. Results: 289 patients were identified as having had both CTCA and ICA. 55 (19%) of these studies were FLASH, 173 (59.9%) prospective, 2 (0.7%) retrospective, 41 (14.2%) calcium score only, and 18 (6.2%) requiring ≥2 contrast studies. [Results are reported FLASH vs Prospective] Diagnostic scans in 92.7% vs 93.6%. Mean BMI (Kgm²): 28 (22-46) vs 30 (18-46). Mean acquisition HR (bpm): 55 (48-70) vs 59 (41-166, median 59). Median dose metoprolol (mg): 5 (0-30) vs 5 (0-50). Median DLP (mGy*cm): 79 (49-351) vs 199 (60-964). There was 58.2% agreement with FLASH studies and ICA versus 67.1% agreement with prospective acquisitions. This was not statistically significant (p=0.26). Conclusion: Our data demonstrates that there is no statistically significant difference between FLASH and prospectively gated CTCA studies within our service. There is however a trend demonstrating that FLASH scans are not as accurate as prospectively gated scans although this is in a relatively small patient population. More studies with larger patient numbers and multi-centre analysis are recommended.